International Health Regulations Implementation and Disease Surveillance in Indonesia: An Analysis of Law No. 17 of 2023 - Bintang Corvi Diphda; Putri Alyaa Safira; ⁠⁠Fabio Philbert Theodore; Clarissa Nazwa Kurniawati; Sultan Baariq Hafizh; Fiorenza Audrey Purnomo; Nur Anisa Fadila Umar; Henny Rosalinda (Sean Institute, 2026)
This article examines how Law No. 17 of 2023 translates International Health Regulations (IHR) obligations into Indonesia’s disease surveillance governance. The article uses Global Health Governance and the idea of global governance as state transformation to explain how international standards become operational through domestic legal and institutional change. Methodologically, the article adopts a qualitative single-case study design and uses a structured desk review of Law No. 17 of 2023, WHO assessments, Indonesian policy documents, surveillance evaluations, and relevant academic literature. The findings show that Law No. 17 of 2023 strengthens Indonesia’s formal surveillance architecture by embedding screening and surveillance within primary health care, clarifying central and regional government responsibilities, supporting laboratory-based detection, integrating health information systems, linking surveillance with outbreak preparedness and emergency response, and recognizing multisectoral coordination for communicable disease control. However, the law’s practical effect remains constrained by decentralization, unequal subnational capacity, weak infrastructure in remote areas, fragmented data systems, limited interoperability, workforce shortages, and coordination problems across sectors and levels of government. The article implies that Law No. 17 of 2023 represents an important domestic legal translation of IHR obligations, but legal formalization alone is insufficient to ensure surveillance performance. Stronger operational consolidation is still needed so that surveillance can function consistently across Indonesia’s institutions, territories, and sectors